Financial Reforms, Financial Openness, and Corporate Borrowing : International Evidence - Detragiache, Enrica; Agca, Senay; De Nicolo, Gianni (Washington, D.C. : International Monetary Fund, 2007)
We study how credit market deregulation and increased international financial openness have changed corporate borrowing. The evidence comes from a large panel of publicly traded firms in 38 countries over the period 1994-2002. Reforms are measured with a comprehensive new index that tracks six separate dimensions. We find that these transformations have increased leverage and lengthened debt maturity in advanced economies, as expected, suggesting that in these countries corporate credit markets have become deeper. In emerging economies, the picture is more mixed: more international openness has led to more leverage but shorter debt maturity. Financial sector reforms have reduced leverage, while their effects on debt maturity have differed depending on the type of reform. Importantly, the differential impact of openness and reforms on the leverage and debt maturity of firms in advanced and emerging market countries also emerges when we distinguish between firms that are potentially financially constrained and firms that are not. These findings suggest that in emerging economies fundamental institutional weaknesses make it difficult to secure the benefits of international financial openness and domestic financial reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet